P-40 The changing face of training in light of the COVID-19 pandemic. (20th March 2022) - Rowley, Grace; Billet, Hannah; Charles, Max; Dewhurst, Felicity; Gouldthorpe, Craig; Howorth, Kate; Huggin, Amy; Kavanagh, Emily; Kiltie, Rachel; Little, Andrew; Mastaglio, Francesca; Simkiss, Lauri; et al.
Abstract : Background: The Covid-19 pandemic brought many changes to palliative care. Services had to rapidly adapt to provide the structures needed in challenging and evolving conditions. Service workforces contained palliative medicine trainees who, alongside providing clinical care, were also required to fulfil training competencies. This study explored the impact of the pandemic on training (both positive and negative) including the adaptations made and the ongoing legacies. Method: A UK-wide survey was distributed to all palliative medicine trainees through Association of Palliative Medicine regional trainee representatives. Responses were received from over 70% of deaneries. The survey collected qualitative and quantitative data and considered changes to the workplace and training. Results: All trainees recognised changes to consultations across all care settings with a particular increase in telephone and video interactions. There were numerous positive work opportunities. Trainees were involved in policy, guideline and educational resource development and complex clinical situations such as the withdrawal of non-invasive ventilation. Education changed. Initially formal education provision was suspended. Subsequently, the shift to virtual platforms had the benefit of reducing travel and increasing flexibility allowing easier access to national speakers and shared resources. Consequently, for many regions it has remained in place. The survey respondents highlighted challenges in assessments particularly Direct Observation of Procedural Skills (DOPS) and Mini-Clinical Examinations (mini-CEX) due to a combination of increased workload, reduced joint reviews and limitations on movement between different clinical areas. Conclusion: The survey showed that there were definite challenges for trainees that arose from the Covid-19 pandemic however there were also positive changes particularly around education. Further work should explore whether there needs to be a greater emphasis on virtual consultation skills in training.